Exploring the multidimensional symptom experience in patients with inflammatory bowel disease—a contemporaneous network analysis - Di, Yunzheng; Chen, Yamei; Zhu, Xiaoping; Wang, Rong; Zhang, Sijia; Sun, Pengcheng (Frontiers in Medicine, 2025)
AimTo explore and visualize the relationships among multiple symptoms in patients with inflammatory bowel disease (IBD) and present empirical evidence for establishing personalized and precise symptom management strategies.DesignThis is a quantitative research study conducted between May 2024 and March 2025 using a correlational research design.MethodsA total of 324 individuals diagnosed with IBD and hospitalized in Shanghai completed the Symptom Cluster Scale for Inflammatory Bowel Disease (SCS-IBD). We conducted multiple linear regression analysis to investigate factors related to the severity of overall IBD symptoms. After accounting for covariates, contemporaneous networks were constructed using all 18 symptoms.ResultsIt was determined that active IBD, years since IBD diagnosis, or those who have not received medication and surgery tend to have more severe IBD symptoms. Although fatigue was the most frequent (74.07%) and severe symptom (2.37 ± 1.161) in IBD, the strength centrality of fatigue was lower than that of weight loss and diarrhea. Weight loss (rs = 4.414, rscov = 5.202) and diarrhea (rs = 4.489, rscov = 5.109) are the core symptoms based on exhibiting the highest strength centrality values in both networks, regardless of whether covariates are included or not.ConclusionOur findings identified that IBD experienced a heavy symptom burden of a severe nature, with weight loss and diarrhea being core symptoms, regardless of covariate adjustment.